Planting Tolerance Attitudes Of Children In Inclusion Paud (Study In Anyelir PAUD, Semarang City) - Prawiratama Putra, Ricky Ariyanto; Diana, Diana (BELIA: Early Childhood Education Papers, 2021)
This study aims to describe the planting of tolerance in early childhood in PAUD Anyelir, Tinjomoyo Village, Banyumanik District. The study describes the cultivation of tolerance in early childhood and knows the supporting factors and factors that hinder the cultivation of tolerance in Anyelir PAUD. The method used is a qualitative descriptive research method case study design using data analysis techniques based on the theory of Miles Huberman. In collecting primary data data collection techniques through interviews and observation methods. Interviewing school administrators and PAUD Anyelir teachers. Besides that, it also uses supporting data in the form of references to books, journals and documents as secondary data. Then the researcher used a descriptive analysis method which consisted of three steps: First, data reduction. Second, presentation of data. Third, conclusions. The results of the analysis obtained regarding the cultivation of tolerance attitudes in early childhood in PAUD Anyelir Tinjomoyo Semarang City, were seen from the cultivation of tolerance, organizing, monitoring learning, learning evaluation, and reporting of learning results referring to the standard process, and the standard assessment module that comes from STPPA, content standards, process standards and assessment standards. The cultivation of tolerance in Anyelir PAUD is also influenced by supporting factors in the form of the implementation of learning in the form of existing facilities and infrastructure, namely educational games used as other media, classrooms, inspirational classes and also teacher cooperation in developing learning programs. Meanwhile, the inhibiting factors are incomplete facilities, and the arrival hours of children who are released, for learning at Anyelir PAUD is in accordance with the applicable standards, namely the national PAUD standard. So that the managers and teachers should complete the facilities and then determine the child's departure time so that it is in accordance with the national PAUD standards so that children's concentration is better in the learning process. Keywords: Tolerance Attitude, Early Childhood, Inclusion PAUD